PENERAPAN FUNGSI PERENCANAAN MANAJEMEN SUMBER DAYA MANUSIA PADA SEKOLAH TINGGI AGAMA ISLAM NEGERI MANDAILING NATAL - Vebri Sugiharto (Program Studi Manajemen Bisnis Syariah STAIN Mandailing Natal, 2021)
Quality human resource management has a positive impactt on changes and developments in education at State Islamic Religious Colleges (PTKIN). Therefore, human resource management planning in managing and developing state Islamic religious colleges is very necessary. This study aims to determine the application of the planning function of human resource management at the STAIN Mandailing Natal in an effort to improve reliable and competitive human resources. The results showed that the implementation of the planning function of human resource management at the STAIN Mandailing Natal was carried out based on the principles and functions of human resource management. The development and training of educators and education staff is carried out as a provision for quality academic development which is carried out consistently in the form of educational activities, training and scientific development.